2015
DOI: 10.1371/journal.pone.0137735
|View full text |Cite
|
Sign up to set email alerts
|

Trials of Improved Practices (TIPs) to Enhance the Dietary and Iron-Folate Intake during Pregnancy- A Quasi Experimental Study among Rural Pregnant Women of Varanasi, India

Abstract: BackgroundBehavior Change Communications (BCC) play a decisive role in modifying socio-cultural norms affecting the perception and nutritional practices during pregnancy.ObjectiveTo examine the effectiveness of ‘Trials of Improved Practices’ (TIPs) on dietary and iron-folate intake during pregnancy.DesignCommunity based quasi experimental study with a control groupSettingFour villages of Chiraigaon Community Development Block of Varanasi, India from May 2010 and recruited from August 2010. End line assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 21 publications
2
67
1
7
Order By: Relevance
“…• Compliance was 86 % in the treatment group v. 48 % in the control group • Side-effects, misconceptions about the length of treatment and forgetting to take IFA were barriers Shivalli et al (37) 2015 India Trials of Improved Practices to improve IFA supplement intake in pregnant women. IFA supplements were either purchased or received through the health-care system…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
See 2 more Smart Citations
“…• Compliance was 86 % in the treatment group v. 48 % in the control group • Side-effects, misconceptions about the length of treatment and forgetting to take IFA were barriers Shivalli et al (37) 2015 India Trials of Improved Practices to improve IFA supplement intake in pregnant women. IFA supplements were either purchased or received through the health-care system…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
“…vomiting, nausea, dizziness) and forgetfulness. In addition, eight studies reported that more than 75 % of women had high compliance (taking ≥70 % of tablets) with IFA supplementation when there was a consistent supply of IFA supplements from the community level, either with or without IFA supplements delivered through health facilities (21,24,25,28,(34)(35)(36)(37) . In India, compliance was higher (62 %) among mothers who were counselled by health workers on when, how and why IFA supplementation is important than among those who did not receive guidance (20) .…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
See 1 more Smart Citation
“…Shivalli S. y cols. 2015 (17) India La ingesta proteica promedio fue mayor en el GI que en el GC (p< 0,05). Más de dos tercios de las mujeres del GI incorporaron una comida extra y sólo un tercio de los controles.…”
Section: Características De Las Estrategias Educativas Empleadasunclassified
“…Asimismo se pondera el incremento del consumo proteico (16,17,38) y la adecuación del aporte calórico (16,26,38,46).…”
Section: Características De Las Estrategias Educativas Empleadasunclassified